Managing Protected Areas in Central and Eastern Europe Under Climate Change - Rannow, Sven; Neubert, Marco (Springer Nature, 2014)
Climate Change; Nature Conservation; Fish & Wildlife Biology & Management; Landscape/Regional and Urban Planning; Applied Ecology